"Painful legs and moving toes" associated with polyneuropathy. Issue 5 (May 1983) - Montagna, P; Cirignotta, F; Sacquegna, T; Martinelli, P; Ambrosetto, G; Lugaresi, E
Abstract : Three patients showing clinical and electrophysiological evidence of peripheral neuropathy also suffered from the syndrome of "painful legs and moving toes". Polygraphic recordings during wakefulness and sleep were consistent with the hypothesis that pathological afferent discharges arising peripherally may induce, via the spinal cord, motor excitation and pain. A severe disruption of the pattern of sleep was found in all cases.